Peran Gender Dalam Masyarakat Arab Pra-Islam - Muhammad Dimas Prakoso; Febri Priyoyudanto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The term gender has been heard by many people, but there are nevertheless many people who do not really understand the term correctly. Gender Equality is one of the problems that is generally often discussed by people to accompany the development of contemporary thinking, both inside the pre-Islamic period and in the period after the arrival of Islam. This paper discusses how gender roles were in the pre-Islamic period which at that time was still very thick with patriarchal culture. And the technique used in this study is within the shape of a literature study, namely by using data sources through literature data such as journals, articles, and internet sites without having to conduct interviews and observations to the field. The result of this paper is that inside the pre-Islamic times of arab society the women were in a time of disgrace and were so demeaned that they became a symbol of the scum and filth of society in that era, but everything changed When the Messenger of Rasulullah SAW came to bring islam to this world, and in those days it positioned women in a noble place. Which means that among men and women there's no distinction when in social life.